GAMBARAN FAKTOR PEKERJAAN IBU TERHADAP KERJADIAN STUNTING PADA BALITA USIA 12-59 BULAN DI KENAGARIAN BALINGKA KABUPATEN AGAM - Yuliza Anggraini; Marisa Amalia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Stunting is a chronic nutritional problem caused by a lack of nutrition in the long term, resulting in impaired growth in children. Stunting is also one of the causes of stunted children's height so that they are lower than children of their age. In 2022 the prevalence of stunting in Indonesia has fallen to 21.6% when compared to the previous year which reached 24.4%, but this figure is still far from the government's target in 2024 to be 14% and WHO's target to be 20%. The aim is to find out the description of work factors on the incidence of stunting in toddlers aged 12-59 months in Kenagarian Balingka, Agam Regency. The method uses an analytic descriptive design. Sampling by simple random sampling with a total sample of 55 toddlers aged 12-59 months. The results of the study found that most of the toddlers aged 12-59 months who experienced stunting came from mothers who had jobs as housewives (53.2%). In conclusion, the majority of toddlers who experience stunting in the Balingka district come from mothers who work as housewives (53.2%). Keywords: Mother's Job, Stunting.